Răspuns :
Răspuns:
Explicație pas cu pas:
1x2-[10+7-(X:7:4)+5x2]:8=0
[10+7-(X:7:4)+5x2]:8 = 2
10+7-(X:7:4)+5x2 = 16
17 - (X : 7 : 4) + 10 = 16
X : 7 : 4 = 17 + 10 - 16 = 11
X : 7 = 44
X = 308
1 × 2 - [ 10 + 7 - ( X : 7 : 4 ) + 5 × 2 ] : 8 = 0
2 - [ 10 + 7 - ( X : 7 : 4 ) + 10 ] : 8 = 0
2 - [ 17 - ( X : 7 : 4 ) + 10 ] : 8 = 0
[ 17 - ( X : 7 : 4 ) + 10 ] : 8 = 2 - 0
[ 17 - ( X : 7 : 4 ) + 10 ] : 8 = 2
17 - ( X : 7 : 4 ) + 10 = 2 × 8
17 - ( X : 7 : 4 ) + 10 = 16
17 - ( X : 7 : 4 ) = 16 - 10
17 - ( X : 7 : 4 ) = 6
X : 7 : 4 = 17 - 6
X : 7 : 4 = 11
X : 7 = 11 × 4
X : 7 = 44
X = 44 × 7
X = 308
2 - [ 10 + 7 - ( X : 7 : 4 ) + 10 ] : 8 = 0
2 - [ 17 - ( X : 7 : 4 ) + 10 ] : 8 = 0
[ 17 - ( X : 7 : 4 ) + 10 ] : 8 = 2 - 0
[ 17 - ( X : 7 : 4 ) + 10 ] : 8 = 2
17 - ( X : 7 : 4 ) + 10 = 2 × 8
17 - ( X : 7 : 4 ) + 10 = 16
17 - ( X : 7 : 4 ) = 16 - 10
17 - ( X : 7 : 4 ) = 6
X : 7 : 4 = 17 - 6
X : 7 : 4 = 11
X : 7 = 11 × 4
X : 7 = 44
X = 44 × 7
X = 308